APPLICATIONS OF X-RAY DIFFRACTION (XRD) ANALYSIS IN FORENSIC EXAMINATION (Modern American Journal of Medical and Health Sciences, 2026)
This article analyzes the potential applications of X-ray diffraction (XRD) methods in forensic examination. XRD stands out for its high accuracy, non-destructive analysis, and reproducibility in determining the phase composition of crystalline substances. The study demonstrates the effectiveness of XRD in identifying and comparing forensic materials such as explosives, soil, paints, and pharmaceutical products. Based on international experience and practices in Uzbekistan, the article highlights the reliable use of this method as evidence in judicial and investigative processes. The results confirm the significant scientific and practical value of XRD technology in forensic expertise.